Degradation of Phenol in Aqueous Solution with Modified Ti/SnO2-Sb Electrode - Wang, Yan; Wei, Jianxia; Zhu, Huaigong; Zhao, Luyang; Zhang, Hailong; Zhang, Xubin (Asian Journal of Chemistry, 2015)
Electrochemical degradation of phenol in aqueous solution was investigated over Ti/SnO2-Sb anode prepared by coating dyrolysis method. The effect of Sb content on the structure and electrocatalytic performance of Ti/SnO2-Sb anode had been studied. The surface coating structure was characterized by scanning electronic microscopy. The analysis showed that a limited amount of doping Sb (moral ratio of Sn:Sb = 100:5) could improve the surface structure of the layer and an over-doping of Sb had a negative impact. Furthermore, the effects of the applied current density and supporting electrolyte were studied by timing cyclic voltammetry and timing ultraviolet spectroscopy method. The experimental results indicated that about 100 % phenol was degraded at a constant current of 10 mA/cm-2 with the supporting electrolyte solution of sodium sulfate without a significant increase in potential within 12 h.